2012
DOI: 10.1177/0194599812451438a56
|View full text |Cite
|
Sign up to set email alerts
|

Are Prophylactic Antibiotics Required in Thyroidectomies?

Abstract: loud music volume and lack of awareness about potential hearing damage. We wanted to evaluate current trends in music listening behaviors, perception of personal risk, and hearing loss education in 2 musically inclined demographics. Method: An anonymous online 89-question survey instrument was made available to a convenience sample of visitors on both VH1.com and CMT.com Web sites. Respondents were queried about attitudes and behaviors related to hearing protection and noise exposure. A P < .05 value was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many head and neck procedures, including thyroidectomy, parathyroidectomy, salivary gland excisions, and neck dissections, are considered clean surgeries. Considering the low infection rates without the use of antibiotics in case series, prophylaxis may not be necessary for thyroidectomy (0.001%-2.6%; total n = 14,114) [118][119][120][121][122][123][124][125] and parotidectomy (0.01%-10.4%; total n = 334). [126][127][128] A case series using cefazolin 129 (n = 438), a retrospective cohort using cefuroxime 130 (n = 807), and an RCT using sulbactam/ampicillin 131 (n = 500) showed no difference in postoperative infection rates with and without single intraoperative antibiotic use in clean head and neck surgery (1.1% vs 0.57%, 0.4% vs 1.4%, and 0.01% vs 0.02%, respectively).…”
Section: Otologicmentioning
confidence: 99%
“…Many head and neck procedures, including thyroidectomy, parathyroidectomy, salivary gland excisions, and neck dissections, are considered clean surgeries. Considering the low infection rates without the use of antibiotics in case series, prophylaxis may not be necessary for thyroidectomy (0.001%-2.6%; total n = 14,114) [118][119][120][121][122][123][124][125] and parotidectomy (0.01%-10.4%; total n = 334). [126][127][128] A case series using cefazolin 129 (n = 438), a retrospective cohort using cefuroxime 130 (n = 807), and an RCT using sulbactam/ampicillin 131 (n = 500) showed no difference in postoperative infection rates with and without single intraoperative antibiotic use in clean head and neck surgery (1.1% vs 0.57%, 0.4% vs 1.4%, and 0.01% vs 0.02%, respectively).…”
Section: Otologicmentioning
confidence: 99%
“…Clean H&N surgery incudes thyroidectomy, parathyroidectomy, salivary gland excisions, congenital neck masses (branchial cleft, thyroglossal duct, and dermoid cysts), nerve sheath tumors, and neck dissections. Considering the low infection rates without the use of antibiotics reported in different case series, prophylaxis may not be necessary for thyroidectomy [120][121][122][123][124][125][126][127] and parotidectomy. [128][129][130] An RCT of 500 patients showed no difference in SSI rates with or without a single dose of intraoperative sulbactam/ampicillin in clean H&N surgery (0.01% vs 0.02%).…”
Section: Is Antibiotic Prophylaxis Required For Benign And/or Cleanmentioning
confidence: 99%
“…There are some publications in the indexed literature regarding low infection rates without the use of antibiotics in different case series; these data suggest prophylaxis might be not necessary for thyroidectomy [11][12][13][14][15][16][17][18] and parotidectomy. 19,20 A randomized controlled trial including 500 patients showed no difference in SSI rates with or without a single dose of intraoperative ampicillin/sulbactam in clean head and neck surgery (thyroidectomy; 0.01% vs 0.02%).…”
Section: Discussionmentioning
confidence: 99%